(untitled) (Journal of the College of Basic Education, 2026)
This paper deals with: Provisions for those who rebel against the ruler in Islamic jurisprudence and Iraqi penal law (a comparative study). The first section deals with: The concept of rebels against rulers, the evidence for the prohibition of rebellion, and the conditions for combating them. The second section deals with: The treatment of those who have left the ruler. While the third section deals with: Guaranteeing those who rebel against the ruler and seek help from others and their punishment.